Missense Gamma-Aminobutyric Acid Receptor Polymorphisms Are Associated with Reaction Time, Motor Time, and Ethanol Effects in Vivo - García-Martín, Elena; Ramos, María I.; Cornejo-García, José A.; Galván, Segismundo; Perkins, James R.; Rodríguez-Santos, Laura; Alonso-Navarro, Hortensia; Jiménez-Jiménez, Félix J.; Agúndez, José A. G. (Frontiers in Cellular Neuroscience, 2018)
Background. The Gamma-aminobutyric acid type A receptor (GABA-A receptor) is affected by ethanol concentrations equivalent to those reached during social drinking. At these concentrations, ethanol usually causes impairment in reaction and motor times in most, but not all, individuals. Objectives. To study the effect of GABA-A receptor variability in motor and reaction times, and the effect of low ethanol doses. Methods. Two hundred and fifty healthy subjects received one single dose of 0.5 g/Kg ethanol per os. Reaction and motor times were determined before ethanol challenge (basal), and when participants reached peak ethanol concentrations. We analyzed all common missense polymorphisms described in the 19 genes coding for the GABA-A receptor subunits by using TaqMan probes. Results. The GABRA6 rs4454083 T/C polymorphisms were related to motor times, with individuals carrying the C/C genotype having faster motor times, both, at basal and at peak ethanol concentrations. The GABRA4 rs2229940 T/T genotype was associated to faster reaction times and with lower ethanol effects, determined as the difference between basal reaction time and reaction time at peak concentrations. All these associations remained significant after correction for multiple comparisons. No significant associations were observed for the common missense SNPs GABRB3 rs12910925, GABRG2 rs211035, GABRE rs1139916, GABRP rs1063310, GABRQ rs3810651, GABRR1 rs12200969 or rs1186902, GABRR2 rs282129, and GABRR3 rs832032. Conclusions. This study provides novel information supporting a role of missense GABA-A receptor polymorphisms in reaction time, motor time and effects of low ethanol doses in vivo.